Rapid Urban Malaria Appraisal (RUMA) IV: Epidemiology of urban malaria in Cotonou (Benin) - Akogbeto Martin (Malaria Journal, 2006)
Abstract Background An estimated 40 % of the population in Benin lives in urban areas. The purpose of the study was to estimate malaria endemicity and the fraction of malaria-attributable fevers in health facilities in Cotonou. Methods A health care system evaluation and a series of school parasitaemia surveys and health facility-based surveys were carried out during the dry season in of 2003, applying standard Rapid Urban Malaria Appraisal (RUMA) methodology. This study was part of a multi-site assessment supported by the Roll Back Malaria Partnership. Results The field work was carried out in February-March 2003. In 2002 and out of 289,342 consultations in the public health facilities of Cotonou there were 100,257 reported simple malaria cases (34.6%) and 12,195 complicated malaria cases (4.2%). In the school parasitaemia surveys, a malaria infection was found in 5.2 % of all samples. The prevalence rates of parasitaemia in the centre, intermediate and periphery zones were 2.6%, 9.0% and 2.5%, respectively. In the health facility surveys the malaria infection rates in presenting fever cases were 0% (under one year old), 6.8% (one to five years old), 0% (> five to 15 years old) and 0.9% (over 15 years old), while these rates in the control group were 1.4%, 2.8%, 1.3% and 2.0%. The malaria-attributable fractions among presenting fever cases were 0.04 in the one to five years old and zero in the three other age groups. Hence, malaria played only a small role in fever episodes at the end of the dry season. In total, 69.2% of patients used a mosquito net the night before the survey and 35.1% used an insecticide-treated net, which was shown to be protective for an infection (OR = 0.23, 95% CI 0.07–0.78). Travelling to a rural area (5.8% of all respondents) did not increase the infection risk. Conclusion The homogenously low malaria prevalence might be associated with urban transformation and/or a high bednet usage. Over-diagnosis of malaria and over-treatment with antimalarials was found to be a serious problem.